Quality Control Using the Quality Control Circle (QCC) Method to Reduce Product Defects on Cylinder Rotogravure at PT XYZ - Hendra Wahyu; Farliana Sutartiah; Pandena Kicky Basuki Putri (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
PT XYZ manufactures rotogravure cylinders as printing masters for flexible packaging. The primary issue was the high reprocessing ratio (reprocess NG) during January–November 2024 and 2025, reaching Year-to-Date (YTD) averages of 3.89% and 2.37% respectively, both exceeding the company's 2.00% tolerance target. This study aims to identify the dominant defects, analyze their root causes, and formulate corrective actions using the Quality Control Circle (QCC) method through the PDCA (Plan-Do-Check-Action) cycle and Seven Tools. Pareto chart analysis revealed three dominant defects accounting for 82.21% of the cumulative problems: Bubble (34.62%), Pinhole (29.32%), and Corrosion (18.27%). Fishbone diagram analysis indicated root causes stemming from unstable chemical dosing flow, difficulty cleaning the copper nugget basket, lack of standardized instructions for material replenishment and oiling, and humid storage conditions. Corrective actions included replacing the dosing pump hose, modifying the copper nugget cleaning tool, establishing an enclosed storage area, and developing new Work Instructions equipped with Visual Control Checks. Implementation results for January–March 2026 demonstrated the effectiveness of the QCC method, marked by a significant reduction in defects until the defect ratio was suppressed below the company's target of 2.00%, along with cost savings of Rp30,213,408 over three months.